Pengaruh Umur Perusahaan dan Audit Tenure pada Kecepatan Publikasi Laporan Keuangan - Jeva N., Irafitriana; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi, 2015)
Time of publication of financial reports is an important characteristic for accounting information because the promptly available historical information will influence the users of financial reports in economic decision-making process. The objective of this research was to determine the effect of firm age and audit tenure to the time of publication of financial reports. Total samples taken 93 firms listed in Indonesia Stock Exchange (IDX)  for three years. Samples in this research were taken by probability sampling method using stratified random sampling. Multiple linear regression was the analysis technique used in this research. Based on the analysis results it was found that the firm age influenced positively on the time of publication of financial reports. This proved that the older the firm age then its time of publication of financial reports increased or tended to increase. On the other hand, the audit tenure influenced negatively on the time of publication of financial reports. This indicated that the longer the audit tenure, the time of publication of financial reports to IDX decreased or tended to decrease.
Keywords: firm age, audit tenure, time of publication